MiRNAs in urine: a mirror image of kidney disease?. (April 2015) - Papadopoulos, Theofilos; Belliere, Julie; Bascands, Jean-Loup; Neau, Eric; Klein, Julie; Schanstra, Joost P
<x xml:space="preserve">Abstract</x> miRNAs are short non-coding RNAs that control post-transcriptional regulation of gene expression. They are found ubiquitously in tissue and body fluids and participate in the pathogenesis of many diseases. Due to these characteristics and their stability, miRNAs could serve as biomarkers of different pathologies of the kidney. Urine is a non-invasive reservoir of molecules, especially indicative of the urinary system. In this review, we focus on urinary miRNAs and their potential to serve as biomarkers in kidney disease. Past studies show that urinary miRNAs correlate with renal dysfunctions and with processes involved in the pathophysiology. However, these studies also stress the need for future research focusing on large-scale studies to confirm the usability of urinary miRNAs as diagnostic and/or prognostic markers of different kidney diseases in clinical practice.